Effects of Levodopa on Impairments to High-Level Vision in Parkinson's Disease - Anderson, Stephen; Stegemöller, Elizabeth L. (Frontiers in Neurology, 2020)
Studies have reported that Parkinson's disease (PD) is associated with impairments on cognitive visual tasks. However, the effects of dopamine on cognitive vision remain equivocal. The purpose of this study was to examine performance on cognitive vision tasks in persons with PD and the effects of levodopa on these tasks. Fourteen individuals with PD and 14 age- and sex-matched healthy older adults completed the study. Participants with PD completed the visual tasks following a 12-h withdrawal of dopaminergic medication and again 1 h after taking 1.5 times their normal dose of levodopa. Healthy older adults completed the visual tasks twice using the same session format. Five complex visual tasks were completed, including line discrimination, object discrimination, facial discrimination, visual working memory, and object rotation. The Unified Parkinson's Disease Rating Scale was also collected off and on medication. Participants with PD performed significantly worse than the healthy older adults across all five visual tasks. There were no significant differences in performance between the off and on medication state in persons with PD. This finding indicates either that dopamine deficiency may not be responsible for cognitive visual impairments in PD or that cognitive visual impairments in PD might simply be the result of deficits in more basic visual processing.